2002
DOI: 10.1172/jci16242
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2 mutations in late-onset focal segmental glomerulosclerosis: R229Q is a common disease-associated allele

Abstract: Mutations in NPHS2, encoding podocin, have been identified in childhood onset focal and segmental glomerulosclerosis (FSGS). The role of NPHS2 in adult disease is less well defined. We studied 30 families with FSGS and apparent autosomal recessive inheritance and 91 individuals with primary FSGS. We screened family members for NPHS2 mutations. NPHS2 mutations appeared to be responsible for disease in nine of these families. In six families, the affected individuals were compound heterozygotes for a nonconserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 31 publications
7
103
0
3
Order By: Relevance
“…We predicted the pathogenicity of the so-far published rare associ- -Hamed et al, 2013;Berdeli et al, 2007;Bertelli et al, 2003;Buscher et al, 2010;Caridi et al, 2001;Chernin et al, 2010;Jungraithmayr et al, 2011;Karle et al, 2002;Lipska et al, 2013;Machuca et al, 2009;Megremis et al, 2009;Ruf et al, 2004;Sadowski et al, 2015;Santin et al, 2009;Santin et al, 2011;Tonna et al, 2008;Tsukaguchi et al, 2002;Voskarides et al, 2008), we found 18 patients (17.0%) to carry benign p.R229Q associations ( (He et al, 2007).…”
Section: The Expected Frequency Of Individuals With [Pr229q];mentioning
confidence: 79%
See 1 more Smart Citation
“…We predicted the pathogenicity of the so-far published rare associ- -Hamed et al, 2013;Berdeli et al, 2007;Bertelli et al, 2003;Buscher et al, 2010;Caridi et al, 2001;Chernin et al, 2010;Jungraithmayr et al, 2011;Karle et al, 2002;Lipska et al, 2013;Machuca et al, 2009;Megremis et al, 2009;Ruf et al, 2004;Sadowski et al, 2015;Santin et al, 2009;Santin et al, 2011;Tonna et al, 2008;Tsukaguchi et al, 2002;Voskarides et al, 2008), we found 18 patients (17.0%) to carry benign p.R229Q associations ( (He et al, 2007).…”
Section: The Expected Frequency Of Individuals With [Pr229q];mentioning
confidence: 79%
“…segmental glomerulosclerosis (FSGS), typically diagnosed in the sec-ond or third decade of life and leading to end-stage renal disease between 10 and 50 years of age (Berdeli et al, 2007;Karle et al, 2002;Lipska et al, 2013;Machuca et al, 2009;Ruf et al, 2004;Sadowski et al, 2015;Santin et al, 2011;Tsukaguchi et al, 2002).…”
mentioning
confidence: 99%
“…Although it is generally regarded as idiopathic, significant progress has been made in defining the molecular basis of inherited forms of nephrotic syndrome and FSGS. 2 The glomerular barrier, where primary urine formation occurs, is comprised of a fenestrated endothelium, the basement membrane and highly specialized visceral epithelial podocytes. Their foot processes, interdigitated on top of the outer surface of the basement membrane, are separated by the slit diaphragm, a specific intercellular junction with an electro-dense zipper-like structure.…”
Section: Discussionmentioning
confidence: 99%
“…R229Q was once believed to be harmless because it occurs in 2-4% of healthy individuals [49]. However, further studies have shown that R229Q decreases podocin binding to nephrin [50]. Although it may have only a weak biological effect, it is now known that compound heterozygosity for R229Q and p.A284V maybe characteristic of late childhood- or adult-onset SRNS [50,51,52].…”
Section: Nphs2 Mutationsmentioning
confidence: 99%
“…However, further studies have shown that R229Q decreases podocin binding to nephrin [50]. Although it may have only a weak biological effect, it is now known that compound heterozygosity for R229Q and p.A284V maybe characteristic of late childhood- or adult-onset SRNS [50,51,52]. Santin et al [53] also found that the phenotypes of late childhood- and adult-onset SRNS are more similar to each other than to early childhood-onset SRNS.…”
Section: Nphs2 Mutationsmentioning
confidence: 99%